Economic burden of non-malignant blood disorders across Europe: A population-based cost study - Luengo-Fernandez, R; Burns, R; Leal, J (Elsevier, 2016)
Background: Blood disorders comprise a wide range of diseases including anaemia, malignant blood disorders, and haemorrhagic disorders. Although they are a common cause of disease, no systematic cost-of-illness studies have been done to assess the economic effect of non-malignant blood disorders in Europe. We aimed to assess the economic burden of non-malignant blood disorders across the 28 countries of the European Union (EU), Iceland, Norway, and Switzerland. Methods: Non-malignant blood disorder-related costs (WHO International Classification of Diseases, 10th revision [ICD] D50-89) were estimated for 28 EU countries, Iceland, Norway, and Switzerland for 2012. Country-specific costs were estimated with aggregate data on morbidity, mortality, and health-care resource use obtained from international and national sources. Health-care costs were estimated from expenditure on primary care, outpatient care, emergency care, hospital inpatient care, and drugs. Costs of informal care and productivity losses due to morbidity and early death were also included. To these costs we added those due to malignant blood disorders (ICD-10 C81-96 and D47) as estimated in a Burns and colleagues' companion Article to obtain the total costs of blood disorders. Findings: Non-malignant disorders of the blood cost the 31 European countries €11 billion in 2012. Health-care costs accounted for €8 billion (75% of total costs), productivity losses for €2 billion (19%), and informal care for less than €1 billion (6%). Averaged across the European population studied, non-malignant disorders of the blood represented an annual health-care cost of €159 per ten citizens. Combining malignant and non-malignant blood disorders, the total cost of blood disorders was €23 billion in 2012. Interpretation: Our study highlights the economic burden that non-malignant blood disorders place on European health-care systems and societies. Our study also shows that blood disorder costs were evenly distributed between malignant and non-malignant blood disorders. Our results should be of use to decision makers and research-funding authorities charged with allocating health-care resources and research funds. Funding: European Hematology Association.